2009
DOI: 10.1002/jsfa.3816
|View full text |Cite
|
Sign up to set email alerts
|

Chickpea protein isolates obtained by wet extraction as emulsifying agents

Abstract: The method applied for isolate preparation influenced to an appreciable extent the ability of proteins to adsorb to the oil-water interface and stabilize emulsions during long-time ageing or following heat treatment or freezing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
56
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(59 citation statements)
references
References 35 publications
1
56
0
Order By: Relevance
“…At the pI (~4.5-5.0), legume proteins assume a net neutral charge and tend to aggregate and fall out of solution. Isoelectric precipitation typically yields mainly globulin proteins (Papalamprou et al 2010), whereas other extraction methods, such as salt extraction, yield isolates comprised of a mixture of globulins and albumins (Liu et al 2008). Protein levels in the present study were comparable to others found in literature.…”
Section: Composition Of Legume Protein Isolatessupporting
confidence: 88%
See 2 more Smart Citations
“…At the pI (~4.5-5.0), legume proteins assume a net neutral charge and tend to aggregate and fall out of solution. Isoelectric precipitation typically yields mainly globulin proteins (Papalamprou et al 2010), whereas other extraction methods, such as salt extraction, yield isolates comprised of a mixture of globulins and albumins (Liu et al 2008). Protein levels in the present study were comparable to others found in literature.…”
Section: Composition Of Legume Protein Isolatessupporting
confidence: 88%
“…In the case of soy, commercially available defatted flour was used as the starting material. Legume flours from seed were defatted in hexane (L'Hocine et al 2006) and then concentrated utilizing a modified isoelectric precipitation procedure (Mondor et al 2009;Boye et al 2010;Papalamprou et al 2010). In brief, the defatted legume flour was dispersed in MQW at a 1 to 10 (w:v; flour:MQW) ratio, followed by pH adjustment to 9.0 with 1.0 M NaOH so as to facilitate protein dissolution.…”
Section: Raw Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Domination of proteins belonging to the globulin fraction over those of the albumin fraction in a chickpea protein isolate obtained by isoelectric precipitation was reported by Sanchez-Vioque et al (1999). Papalamprou et al (2008Papalamprou et al ( , 2010, on the other hand, reported that the chickpea protein isolate obtained by ultrafiltration was made up of a mixture of proteins belonging to both the albumin and the globulin fractions but the albumins were practically absent from the isolate obtained by isoelectric precipitation.…”
Section: Preparation Of Protein Concentrates and Isolatesmentioning
confidence: 85%
“…In addition, according to Chapleau and Lamballerie (2003), a high-pressure treated lupin protein isolate with modified surface adsorption characteristics exhibited improved emulsifying properties with respect to initial oil droplet size and stability against flocculation and creaming, compared to the control. In a very recent paper, Papalamprou et al (2010) studied in a more systematic way the emulsifying properties of a number of chickpea protein isolates differing in composition, with respect to globulins and albumins. The isolates were recovered from alkaline chickpea protein extracts by applying either isoelectric precipitation or ultrafiltration.…”
Section: Emulsifying and Foaming Propertiesmentioning
confidence: 99%